Analysis of bolt-to-laminate interface friction in bolted composite joint with interference-fit. (June 2015) - Yuanxin, D.; Yuan, L.; Kaifu, Z.; Ping, L.; Jian, L.
<x content-type="archive" xml:space="preserve">Abstract</x> This paper presents an analytical model to predict the friction force in carbon fibre-reinforced plastic composite joint, which is caused by surface contact between bolt shank and fastener hole with interference-fit. Based on the plane stress analysis in composite laminate, the approximate value of through-the-thickness friction is calculating according to the Coulomb friction criteria. This model takes into account composite material property, joint geometry dimension, interference and friction coefficient. An interference-fit bolt inserting process simulation using three-dimensional finite element analysis is conducted to verify the analytical model. During the simulation, the friction value is obtained after the bolt exited the hole in the bottom of the specimen, which the bolt shank contacts with hole from top to bottom. The results of two methods are shown well agreement, but the analytical model is higher than which of FEA with different interference-fit percentages and hole diameters, because of some assumptions in modelling.